2010
DOI: 10.1007/s11262-010-0528-x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular analysis of infectious bronchitis viruses isolated in Slovenia between 1990 and 2005: a retrospective study

Abstract: Fifteen infectious bronchitis viruses (IBV) isolated from broiler and broiler breeder flocks in Slovenia between 1990 and 2005 were molecularly characterised. IBV strains were divided into four genotypes by the analysis of the S1 gene region. Four strains belonged to the Massachusetts genotype, one strain was placed into the QX genotype, one strain formed a cluster together with the B1648 strain and nine strains were classified into the 624/I genotype. Nine Slovenian strains of the 624/I genotype formed two su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 13 publications
1
19
0
Order By: Relevance
“…However, seven isolates (11052, 1123, 11036, 9106, 8067, 9011 and 1043) showed different clustering patterns. The discordance of clustering patterns in S1-based tree and other gene-based trees have already been described by others and may be caused by recombination [23,[27][28][29].…”
Section: Discussionsupporting
confidence: 57%
“…However, seven isolates (11052, 1123, 11036, 9106, 8067, 9011 and 1043) showed different clustering patterns. The discordance of clustering patterns in S1-based tree and other gene-based trees have already been described by others and may be caused by recombination [23,[27][28][29].…”
Section: Discussionsupporting
confidence: 57%
“…A recent retrospective study carried out on 123 IBV strains isolated in Italy between 1963 and 1989 revealed that 624I genotype had not only circulated long before its first reporting in 1993, but that in fact it has been one of the major IBV genotypes circulating in the Country at that time (Taddei et al, 2012). Evidence of the presence of this genotype has also been found in Slovenia, where several 624I strains were isolated between 1991 and 1999 (Krapez, Slavec, Barlic-Maganja, & Rojs, 2010), in Poland and South Africa (Capua et al, 1999) and eventually in Russia where 624I genotype was reported in 2002 (Bochkov, Batchenko, Shcherbakova, Borisov, & Drygin, 2006).…”
Section: Introductionmentioning
confidence: 66%
“…The basal location of the 624I strain in both the phylogenetic trees, coupled with the epidemiological data available, suggests that this genotype might have played a role in the emergence of Chinese Q1. This model requires long-distance intercontinental dispersion of the 624I genotype and this possibility is supported by its ability to circulate for extended periods within the same country (Taddei et al, 2012) and beyond a geographical area (Capua et al, 1999;Krapez et al, 2010 (Bochkov et al, 2006). Further investigations are needed since, despite the IBV worldwide dissemination has been observed and accepted for other genotypes (Franzo et al, 2017), the mechanism behind this evidence is not fully understood.…”
Section: Discussionmentioning
confidence: 99%
“…They might therefore represent re-isolations of vaccine strains, although they were isolated from vaccinated chickens with respiratory disease. Similarly, IBV strains that showed a very close relationship to the H120 vaccine strain have been isolated from unvaccinated broiler flocks in Slovenia with respiratory problems (Krapež et al, 2010). Alternatively, these strains might be variants of vaccine strains that have resulted from accumulated point mutations after several passages in chickens.…”
Section: Discussionmentioning
confidence: 99%